Oil and regional development : examples from Algeria and Tunisia - Schliephake, Konrad; Lyew, Merrill D. (New York : Praeger, 1977)
This book is on the regional development and particularly that development base on hydrocarbons in both Algeria and tunisia
Translation of Erdöl und regionale Entwicklung.
Bibliography: p. 195-203.
oo 21/01/2019
Loans
Keywords: Petroleum industry and trade; Economic history; Algeria; Tunisia